Comparison of Mechanical and Enzymatic Methods for the Isolation of Bovine Ovarian Follicles - 임현주; 김동훈(농촌진흥청 축산기술연구소; 임기순(농촌진흥청 축산기술연구소; 임정묵 (Journal of animal reproduction & biotechnology (Online), 2010)
The isolation of preantral follicles from the ovaries of bovine was performed under mechanical and enzymatic methods. A significant increase in the total number of follicles retrieved was detected when tissue chopper was used. Micro-dissection could supply good quality, larger sized follicles (400 to 700 μm) but with the lowest yield (9.0±1.0). The isolated preantral and early antral follicles were cultured for 14 days. Follicles isolated by the mechanical method had a greater growth during a culture period than follicles collected enzymatically. Morphologically normal bovine oocytes from early antral follicles after 14 days culture were 59.6% after culture and after 24 h of maturation culture, 12.9% of in vitro-grown oocytes reached the second metaphase. In conclusion, this study showed that mechanical method can be used effectively to isolate intact preantral follicles from bovine ovaries. KCI Citation Count: 1